2004
DOI: 10.2460/ajvr.2004.65.604
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of cellular, biochemical, and histologic effects of bipolar radiofrequency treatment of canine articular cartilage

Abstract: In this study, bipolar radiofrequency treatment had detrimental effects on normal articular cartilage cells and extracellular matrix with probable long-term clinical consequences. The usefulness of radiofrequency for treatment of osteoarthritic articular cartilage requires further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 35 publications
(40 reference statements)
1
10
0
1
Order By: Relevance
“…This chondrocyte death was evident even though the RF energy was applied to the soft tissues in the joint and not directly to the cartilage. Our findings are consistent with other reports in which significant loss of chondrocyte viability was noted immediately after direct application of RF energy to the cartilage (2)(3)(4)(5)(6)12).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This chondrocyte death was evident even though the RF energy was applied to the soft tissues in the joint and not directly to the cartilage. Our findings are consistent with other reports in which significant loss of chondrocyte viability was noted immediately after direct application of RF energy to the cartilage (2)(3)(4)(5)(6)12).…”
Section: Discussionsupporting
confidence: 93%
“…However, to the author's knowledge, the current literature does not contain documentation of the changes that occur in the articular cartilage following the remote treatment of the soft tissues in the joint with RF energy. Lu et al recently reported the fluid temperatures created in the joint during capsular shrinkage with RF energy (28), and Cook et al reported that cartilage explants incubated in culture media greater than 45ºC lead to chondrocyte death (6). However, the biological response of chondrocytes subjected to indirect RF energy is still unknown.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Die optisch imponierende "Versiegelung" basiert auf einer Denaturierung der Kollagenfasern an der Oberfläche durch erhöhte Temperatur. Diese Strukturveränderung kann zwar die Permeabilität der Matrix reduzieren, dies bewirkt jedoch keine Retention der Proteoglykane im Knorpelgewebe [41,55]. Dagegen geht grundsätzlich der Zellverlust im Bereich der Grenzfläche durch Apoptose/Nekrose sogar mit einem erheblichen Proteoglykanverlust einher [56].…”
Section: Glättungunclassified